Computer simulation of linearized Statcom model. (2020) - Geetha Devi, C.E.; Devanathan, R.
Abstract: Static synchronous condenser (Statcom) is an important device for ensuring power system stability. Statcom dynamic model exhibits nonlinearity. Feedback linearization is applied to Statcom model for ease of control. But this brings in the issue of zero dynamics. In this paper, a method of quadratic linearization is applied to Statcom model which circumvents the zero dynamics issue. Quadratic linearization of Statcom is illustrated through Matlab simulation of Statcom model together with the linearizing transformations. Closed loop simulation of linearized Statcom model is also studied.